Immediate Loading of Implants in the Edentulous Maxilla with a Fixed Provisional Restoration without Bone Augmentation: A Report on 5-Year Outcomes Data Obtained from a Prospective Clinical Trial - Toljanic, Joseph A; Ekstrand, Karl; Baer, Russell A; Thor, Andreas (The International journal of oral and maxillofacial implants, 2016)
Successful immediate loading of implants in the edentulous maxilla has been previously reported. The purpose of this 5-year prospective study was to further assess long-term outcomes following immediate loading of implants in the edentulous maxilla with fixed provisional restorations without the use of bone augmentation procedures. Subjects with edentulous maxillary arches each received six implants placed in native bone without augmentation. Where insufficient posterior bone volume existed, angled implant placement was employed. Fixed provisional restorations were delivered within 24 hours of implant placement. Implant placement locations, insertion torque values, and implant dimensions were recorded. Definitive fixed prostheses were placed within 24 weeks following implantation. Baseline implant site marginal bone levels were measured using periapical radiographs. Baseline peri-implant plaque and bleeding scores were obtained. Subjects were examined 6 months after implant placement and then annually for 5 years with follow-up periapical radiographs and plaque/bleeding scores obtained. Fifty-one subjects received a total of 306 implants. Forty subjects with 232 implants returned for the final follow-up appointment representing a 5-year implant survival proportion of 93% with a mean marginal bone loss of 0.44 ± 1.25 mm for this group. Thirty-nine of these 40 subjects continued to function with fixed restorations with the remaining subject functioning with a non-implant-retained removable prosthesis. Within the limitations of this study, predictable long-term implant rehabilitation outcomes were demonstrated for the edentulous maxilla using an immediate loading protocol without bone augmentation.